COMPARATIVE ACUTE AND CHRONIC SENSITIVITY OF FISH AND AMPHIBIANS: A CRITICAL REVIEW OF DATA. (20th March 2013) - Weltje, Lennart; Simpson, Peter; Gross, Melanie; Crane, Mark; Wheeler, James R.
Abstract The relative sensitivity of amphibians to chemicals in the environment, including plant protection product active substances, is the subject of ongoing scientific debate. The objective of this study was to compare systematically the relative sensitivity of amphibians and fish to chemicals. Acute and chronic toxicity data were obtained from the U.S. Environmental Protection Agency (U.S. EPA) ECOTOX database and were supplemented with data from the scientific and regulatory literature. The overall outcome is that fish and amphibian toxicity data are highly correlated and that fish are more sensitive (both acute and chronic) than amphibians. In terms of acute sensitivity, amphibians were between 10‐ and 100‐fold more sensitive than fish for only four of 55 chemicals and more than 100‐fold more sensitive for only two chemicals. However, a detailed inspection of these cases showed a similar acute sensitivity of fish and amphibians. Chronic toxicity data for fish were available for 52 chemicals. Amphibians were between 10‐ and 100‐fold more sensitive than fish for only two substances (carbaryl and dexamethasone) and greater than 100‐fold more sensitive for only a single chemical (sodium perchlorate). The comparison for carbaryl was subsequently determined to be unreliable and that for sodium perchlorate is a potential artifact of the exposure medium. Only a substance such as dexamethasone, which interferes with a specific aspect of amphibian metamorphosis, might not be detected using fish tests. However, several other compounds known to influence amphibian metamorphosis were included in the analysis, and these did not affect amphibians disproportionately. These analyses suggest that additional amphibian testing is not necessary during chemical risk assessment. Environ. Toxicol. Chem. 2013;32:984–994. © 2013 SETAC